1972
DOI: 10.1042/bj1281097
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship and control of glucose metabolism and lipogenesis in isolated fat-cells. Control of pentose phosphate-cycle activity by cellular requirement for reduced nicotinamide adenine dinucleotide phosphate

Abstract: By using inhibitors and stimulators of different metabolic pathways the interdependence of the pentose phosphate cycle and lipogenesis in isolated fat-cells was studied. Rotenone, which is known to inhibit electron transport in the respiratory chain, blocked glucose breakdown at the site of pyruvate dehydrogenase. Consequently, because of the lack of acetyl-CoA, fatty acid synthesis was almost abolished. A concomitant decrease in pentose phosphate-cycle activity was observed. Phenazine methosulphate stimulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
12
0

Year Published

1973
1973
2007
2007

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(14 citation statements)
references
References 16 publications
2
12
0
Order By: Relevance
“…Quantitative agreement with literature data was also found for the calculated fluxes of several pathways whose intermediates were not directly measured in this study. For example, our model indicated that the PPP supplies 60% of the NADPH needed for fatty acid synthesis in mature adipocytes, which is in excellent agreement with the results of isotopic tracer studies (14,22,24). A current estimate (46) for the oxygen uptake rate of day 14 postinduction 3T3-L1 cells is 2.9 nmol/min per 4ϫ10 5 cells, or 1,147 mmol⅐g DNA Ϫ1 ⅐2 days Ϫ1 (assuming a conversion factor of 18.2 pg DNA/cell; unpublished observation), which is quantitatively similar to the rates calculated in this study (626 and 801 mmol⅐g DNA Ϫ1 ⅐2 days Ϫ1 , respectively, for TCP and collagen cultures at day 16).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Quantitative agreement with literature data was also found for the calculated fluxes of several pathways whose intermediates were not directly measured in this study. For example, our model indicated that the PPP supplies 60% of the NADPH needed for fatty acid synthesis in mature adipocytes, which is in excellent agreement with the results of isotopic tracer studies (14,22,24). A current estimate (46) for the oxygen uptake rate of day 14 postinduction 3T3-L1 cells is 2.9 nmol/min per 4ϫ10 5 cells, or 1,147 mmol⅐g DNA Ϫ1 ⅐2 days Ϫ1 (assuming a conversion factor of 18.2 pg DNA/cell; unpublished observation), which is quantitatively similar to the rates calculated in this study (626 and 801 mmol⅐g DNA Ϫ1 ⅐2 days Ϫ1 , respectively, for TCP and collagen cultures at day 16).…”
Section: Discussionsupporting
confidence: 85%
“…Third, biochemistry textbooks (27,42) and the published literature (12) were consulted to eliminate enzymes thought to be inactive in the fed state. Finally, the following assumptions were applied: 1) glycogen synthesis is negligible (22); 2) fatty acid oxidation is small compared with both lipogenesis and lipolysis (47); 3) the pentose phosphate pathway (PPP) is operating in the oxidative mode (6); and 4) net protein synthesis is small compared with metabolic fluxes (17). The stoichiometric model was rendered into a compound, directed graph, visualized using the Bioinformatics toolbox of MATLAB (MathWorks, Natick, MA), and corrected for missing steps and nonsensical dead ends.…”
Section: Methodsmentioning
confidence: 99%
“…Conversion of glucose-6-phosphate to pyruvate is blocked by fluoride (21), and the rate of the pentose phosphate pathway is augmented by the addition of PMS, an agent which permits rapid oxidation of NADPH to NADP. In cells treated in this manner, the regulation of the pentose phosphate pathway by the NADP/NADPH ratio is bypassed (22)(23)(24)(25). In such a system, the conversion of [ Insulin, where present, was at a concentration of 500 microunits/ml.…”
mentioning
confidence: 99%
“…Greenbaum, Gumaa and McLean (13) have suggested that conitrol of the pentlose phosphate cycle might well be through a shift in the ratio of NAD+ to NADH. This concept of mass action control has also been suggested from studies on fat cells ( 14), and on erythrocytes (1 5 ) .…”
mentioning
confidence: 90%